Analisis Pendampingan Lansia yang Mengalami Penyakit Rheumatoid Arthritis pada Lembaga Kesejahteraan Sosial di Aceh - Iskandar Iskandar; Riyan Mulfianda (Faletehan Health Journal, 2021)
Nowadays, elderly assistance in Social Welfare Institutions is generally carried out by non-medical social workers. This potentially causes a shortcoming in elderly care, resulting on the decreased condition of the elders’ health especially those with a chronic rheumatic diseases. This reasearch aimed to analyze the assistance of elderly with Rheumatoid Arthritis (RA) at Nursing Home Darussa'adah, Lhokseumawe, Aceh Province. The research design was descriptive quantitative with descriptive statistics analysis. The population were all elderly people with rheumatism and the samples were 36 respondents who were selected by using purposive sampling technique. The results of univariate analysis showed that the elderly assistance was mostly categorized poor, namely as many as 19 respondents (52.8%), negative monitoring was obtained by 19 respondents (52.8%), negative education was received by 21 respondents (58.3%), and lack of motivation was gotten by 18 respondents (50%). The results of bivariate analysis showed that there was a relationship between elderly assistance and elderly dependence in elders with chronic RA (p value 0.001). The managers of Social Welfare Institution should coordinate with the local Health Office to request elderly assistance and care by nurses for the elders with chronic rheumatic diseases.